2021
DOI: 10.1093/function/zqab036
|View full text |Cite
|
Sign up to set email alerts
|

AKAP79 Orchestrates a Cyclic AMP Signalosome Adjacent to Orai1 Ca2+ Channels

Abstract: To avoid conflicting and deleterious outcomes, eukaryotic cells often confine signalling molecules to spatially restricted sub-compartments. The smallest signalling unit is the Ca2+ nanodomain, forming near open Ca2+ channels. Ca2+ nanodomains near store-operated Orai1 channels stimulate calcineurin, which activates the transcription factor NFAT1, and both enzyme and target are initially attached to the plasma membrane through the scaffolding protein AKAP79. Here we show that a cAMP signalling nexus also forms… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 59 publications
0
13
0
Order By: Relevance
“…One of the strongest differential candidates was phosphodiesterase 8B (PDE8B), which showed a significant difference in mean LFQ intensities between STIM1 and STIM1A or between STIM1 and STIM1A_D503A pull‐down (STIM1: 37627, STIM1A: 7064 and STIM1A_D503A: 64118; see Data availability); however, only a moderate difference was found in the BiFC experiments, potentially due to the C‐terminal tags required for BiFC or due to an indirect interaction requiring a mediator protein (see Discussion). Because a signaling complex between STIM, ORAI1, and A‐kinase anchoring protein (AKAP79) is critical and essential for efficient activation of the transcription factor NFAT (Kar et al , 2014 , 2021a , 2021b ; Samanta et al , 2015 ) and as Son et al ( 2020 ) showed that the polybasic domains of STIM proteins are necessary for the assembly of this signaling complex, we asked whether PDE8B might also be involved in NFAT translocation by altering cAMP levels. Indeed, forskolin, an activator of adenylate cyclase, has been shown to increase NFAT translocation in osteoblasts (Huang et al , 2010 ) and to increase bisperoxovanadium phosphotyrosyl‐phosphatase inhibitor‐mediated NFAT translocation in Jurkat T cells (Barat & Tremblay, 2003 ).…”
Section: Resultsmentioning
confidence: 99%
“…One of the strongest differential candidates was phosphodiesterase 8B (PDE8B), which showed a significant difference in mean LFQ intensities between STIM1 and STIM1A or between STIM1 and STIM1A_D503A pull‐down (STIM1: 37627, STIM1A: 7064 and STIM1A_D503A: 64118; see Data availability); however, only a moderate difference was found in the BiFC experiments, potentially due to the C‐terminal tags required for BiFC or due to an indirect interaction requiring a mediator protein (see Discussion). Because a signaling complex between STIM, ORAI1, and A‐kinase anchoring protein (AKAP79) is critical and essential for efficient activation of the transcription factor NFAT (Kar et al , 2014 , 2021a , 2021b ; Samanta et al , 2015 ) and as Son et al ( 2020 ) showed that the polybasic domains of STIM proteins are necessary for the assembly of this signaling complex, we asked whether PDE8B might also be involved in NFAT translocation by altering cAMP levels. Indeed, forskolin, an activator of adenylate cyclase, has been shown to increase NFAT translocation in osteoblasts (Huang et al , 2010 ) and to increase bisperoxovanadium phosphotyrosyl‐phosphatase inhibitor‐mediated NFAT translocation in Jurkat T cells (Barat & Tremblay, 2003 ).…”
Section: Resultsmentioning
confidence: 99%
“…However, work by Kar et al in this issue of Function now calls into question the expression of an endogenous AC8 isoform in HEK293 cells. 2 Mass spec and qPCR showed no evidence for AC8 and indicated issues with the commercial AC8 antibody used by Zhang et al Critically, using a sensitive FRET-based cAMP biosensor fused to AKAP79 (“AKAP79-CUTie”), the group also did not find evidence for the production of cAMP driven by store-operated Ca 2+ entry through Orai channels in HEK 293 cells. Their Co-IP evidence suggests that a complex consisting of PKA, calcineurin and NFAT moves close to Orai channels after store depletion.…”
Section: A Perspective On "Akap79 Orchestrates a Cyclic Amp Signaloso...mentioning
confidence: 99%
“…In this issue, Kar and colleagues have revisited one such interaction, namely the intimate connection between store-operated Ca 2+ entry via plasma membrane-localized Orai channels and adenylyl cyclases (ACs) situated adjacent to these channels. 2 This privileged spatial arrangement is important because of the potential for calcium ions to regulate cAMP production by ACs. 3 Conversely, cAMP has reported effects on Ca 2+ influx via Orai channels, 4 potentially creating a tidy local feedback loop between the two messengers.…”
Section: A Perspective On "Akap79 Orchestrates a Cyclic Amp Signaloso...mentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, however AC8 was reported to be expressed in neuronal cells, but not in HEK 293 and various immune cells. Alternatively, AKAP79 alone, bound directly to Orai1, was demonstrated to control Ca 2+calcineurin and cAMP-protein kinase signaling pathways independently of AC8 in separate nanodomains [281]. AKAP79 was identified to associate with the N-terminal segment aa 39-59 of Orai1 which allows upon local Ca 2+ entry through Orai1 the activation of associated calcineurin and rapid translocation of NFAT into the nucleus [282].…”
Section: Adenylyl Cyclase 8 (Ac8)mentioning
confidence: 99%